Updated deterministic radiation transport for future deep space missions. (November 2020) - Slaba, T.C.; Wilson, J.W.; Werneth, C.M.; Whitman, K.
Abstract: NASA's deterministic transport code HZETRN, and its three-dimensional (3D) counterpart, 3DHZETRN, are being used to characterize the space radiation environment over a wide range of scenarios, including future planned missions to the moon or Mars. Combined with available spaceflight measurements, these tools provide the fundamental input for risk models used to quantify possible astronaut health decrements and satisfy agency limits in support of exploration initiatives. Further research is therefore needed to improve radiation transport and nuclear physics models while at the same time continuing to expand the available measurement database (ground-based and spaceflight) to validate such efforts. In this work, significant updates to the deterministic radiation transport models are presented. Charged muons and pions are fully coupled with the existing solutions developed for neutron and light ion (Z ≤ 2) transport. This update includes the 3D nature of pion production as well as the pion interactions, resulting in further production of energetic nucleons within shielding. Additional updates related to low energy proton recoils in hydrogenous materials and capture/decay processes associated with charged pions at rest are also described. Included in this work is the coupling of single and double-differential cross sections from Geant4 into HZETRN and 3DHZETRN. This enables a direct comparison of deterministic and Monte Carlo transport methodologies using the same nuclear databases for specific interactions. Comparisons between Geant4 and 3DHZETRN are shown and establish that the transport methodologies are in excellent agreement when the same cross sections are used. The deterministic codes are also compared to ISS data, and it is found that the updated 3D procedures are within measurement uncertainty (±5%) at cutoff rigidities below 1 GV, which approaches free space conditions.